Rotavirus serotype distribution in northern Brazil trends over a 27 year period pre and post national vaccine introduction - Oliveira, Alessilva (2012)
In Brazil, a rotavirus vaccine was included in the public sector in March 2006. In order to identify a possible effect of vaccination on rotavirus strains we evaluated the distribution of serotypes/genotypes in northern Brazil during pre (1981 2005) and early post (2006 2008) national rotavirus vaccine introduction periods. Of 1286 rotavirus strains, 993 (77.2 per cent) were successfully G typed. G1 strains were detected throughout the years, accounting for the majority of typed isolates (n = 426; 42.9 per cent). G2 rotaviruses displayed a cyclic pattern of occurrence over time, re-emerging recently in early 2006, with detection rates as high as 91 per cent, and remained the predominant circulating strain through 2008. G9 rotaviruses appeared during 1990 1992, re-emerged from 1998 to 2000 and rose to 43 per cent in a gastroenteritis outbreak in northwestern Brazil in 2005. The most common combinations overall were G2P[4] (55.1 per cent; 136/247), and G1P[8] (24.7 per cent; 61/247). Although our data show the predominance of G2P [4] early after vaccine introduction, there is a need for continuous, long-term surveillance of circulating strains to better assess a possible effect of rotavirus vaccination on the strain ecology.